Impact of international donors’ new policy agenda on project collaboration between community-based women organizations and NGOs in the Kibera slums of Nairobi, Kenya - De Feyter, Sophie (Afrika Focus, 2011)
This article first describes the New Policy Agenda (NPA), af market-based ideology iniuencing donor agencies’ strategies for international development. The article then continues to discuss how community-based women organizations (CBWOs) and non-governmental organizations (NGOs) evaluate their collaborations or ‘partnerships’ in practice in the Kibera slums of Nairobi, Kenya. We tested the research hypothesis that the NPA reduces the likelihood of achieving equitable partnerships because of its insistence on ‘contracting’ partners, i.e. creating a patron-client relationship. This was carried out through qualitative research consisting mainly of semi-structured interviews and participatory observation with NGOs and CBWO representatives working in Kibera. Research results show that the contract conditions for CBWOs to enter into a partnership may reduce the chances of the most vulnerable groups in society of obtaining assistance. This ‘contracting’ relationship may also cause a loss of CBWO members’ motivation. The NPA and its emphasis on saving time and money also has a negative impact not only on the external development actors’ knowledge about the development context, but also on the multiple accountabilities in a CBWO-NGO partnership, on the quick-fix nature of the solutions applied to remedy the lack of accountability and on the practical implementation of ‘participatory development’ in Kibera. Key words: development, donor relations, contract, participatory development